Egypt's Identities in Conflict: the political and religious landscape of copts and muslims - Naiem, Girgis (McFarland & Co, 2018)
"Egypt's lack of a common national identity is the basis for much of its internal conflict--Coptic Christians have been particularly affected. Once major contributors to Christian civilization, their influence ended with the 5th century Council of Chalcedon and they endured persecution. With the 7th century Arabization of Egypt, Copts were given dhimma or "protected persons" status"--